Research Progress of Initial Mechanism on Debris Flow and Related Discrimination Methods: A Review - Du, Jun; Fan, Zhong-jie; Xu, Wen-tao; Dong, Lin-yao (Frontiers in Earth Science, 2021)
The initial of debris flow can be classified into two types based on their triggering positions, that is, debris flow from slope and debris flow from gully or channel. For the former, great progress has been achieved on the mechanisms of soil failure and liquefaction. The framework established by a series of theories or laws，such as the Mohr-Coulomb criteria, the unsaturated soil mechanics, and the critical state of soil mass, has been used widely in industry and research. However, the details and discrimination basis for the transformation process from landslide into debris flow still need to be further clarified. Relatively, debris flow from gully or channel is more complex due to its various mass sources and the diversity of processes. Nevertheless, through a great number of case studies and experimental statistics, people have gradually recognized the influential rule and critical condition of factors from landform, hydrology and other aspects on debris flow initiation. Furthermore, based on the theories of granular flow, continuum mechanics and rheological law, some typical event-based scenarios can also be reproduced by different single/two-phase depth integral/average numerical models. However, some key knowledge on mechanism and application level are still insufficient, such as the erosion and entrainment mechanism of materials from different sources, the boundary tractions and materials exchange, as well as the selection of prediction indicators. Three current discriminated methodologies for debris flow initiation, i.e., the safety factor method, the rainfall indicator method, and the comprehensive assessment method, were summarized in this paper. Considering the technical limitation of each methodology, it is believed that the establishment or improvement of a unified, stable, and open access database system for event registration & query, as well as the development of large-scale and high-precision rainfall monitoring are still regarded as the important aspects of debris flow prevention in the future. In addition, as an economic and efficiency means for obtaining information on potential threats and real-time hazard messages, the multi-element method for debris flow is recommended as a long-term reference.